Investment of agricultural machinery in agricultural production of Ukraine - Didur, Volodymyr; Дідур, Володимир Аксентійович; Дидур, Владимир Аксентьевич; Hrytsaienko, Halyna; Грицаєнко, Галина Іванівна; Грицаенко, Галина Ивановна; Hrytsaienko, Ihor; Грицаєнко, Ігор Миколайович; Грицаенко, Игорь Николаевич (My University, 2017)
The article examines the current state and investment of supplying the agriculture with the main types of agricultural machinery. The availability and capacity of combine harvesters and tractors of all brands at agricultural enterprises and households has been analyzed. The issues of agricultural machinery renovation, including the expense of imports, are considered. In order to justify the most effective external funding the investments in agricultural machinery, a comparative analysis of financial leasing conditions and bank lending for purchasing a new tractor and a combine harvester. The prospects for further research have identified the justification for the rational composition and structure of the material and technical basis for the intensification of agriculture in the region.
Инвестирование технического оснащения аграрного производства Украины
Keywords: logistics; finance investments; financial leasing; bank credit; tractors of all brands; combine harvesters